Pelatihan Desain Poster Menggunakan Canva Bagi Siswa SMA Negeri 1 Surabaya - Aris Kusumawati; Sri Hidayati; Raulia Riski; Muhammad Zhahnur Arif; Ridho Rahmatullah; Annisa Nur Salsabilla (Politeknik Negeri Cilacap, 2023)
The rapid development of science and technology has resulted in various applications that can help various human needs, including in terms of design. Currently, there are various online-based design applications that provide a variety of attractive designs that can be accessed for free or for a fee, including Canva. This community service aims to increase the design creativity of SMAN 1 Surabaya students, especially in making poster designs with the Canva application. The results of the training showed that SMA Negeri 1 Surabaya students agreed that the training could increase students' knowledge and skills in making poster designs using Canva, as seen from the results of the questionnaire where 81.33% of students gave very good predicates to the training they had attended. The knowledge gained during the training is expected to be useful for students in the short and long term, namely in the wider scope of student life in the future.